DIVERSIFICATION OF THE SOCIO-ECONOMIC AND SPATIAL DEVELOPMENT OF A SMALL MONO-FUNCTIONAL CITY – THE CASE OF THE CITY OF YUZHNE, UKRAINE - PROVOTAR, Nataliia; VOLKOVA, Anastasiia (Ekonomichna ta Sotsialna Geografiya, 2022)
The article presents an analysis of the functioning of a small monofunctional city in the context of diversification of its development and contemporary approaches to urban planning. Using unique case of the city of Yuzhne by the demographic and socio-economic characteristics, the necessity of diversification of the economy and approaches to determining the city's development strategy through local activism, external grants, and the use of new concepts of urban development are shown. The purpose of the work is to analyze the factors of Yuzhne city development, assess the role of city-forming enterprises and determine the directions of diversification processes in a monofunctional small city. The analysis of the prerequisites for the development of the small monofunctional city of Yuzhne was carried by the indicators of demographic and socio-economic development. In order to assess the city-forming role of enterprises, their impact on the socio-economic development of the city was analyzed in terms of the job offer, housing and social infrastructure construction, participation in the creation of the city center and the arrangement of its public spaces. It was determined that the diversification of the economy of the small monofunctional city of Yuzhne should be carried out in such directions as the development of innovative industries based on the training of qualified personnel in educational institutions and the creation of an innovation park, the development of tourism and recreation. Diversification of approaches to city development aims the involvement of various actors through the local activism, external grants, the use of new approaches and concepts of urban development. Positive changes in the development of the small monofunctional city of Yuzhne are related to the elaboration of strategies for its development based on the concepts of sustainable development, integrated city development, innovative development, smart city, green city, creative city, and inclusive city.

У статті представлено аналіз функціонування малого монофункціонального міста в контексті диверсифікації його розвитку та сучасних підходів до міського планування. На прикладі унікального за демографічними і соціально-економічними характеристиками міста Южне показано необхідність диверсифікації економіки та підходів до визначення стратегії розвитку міста за рахунок місцевого активізму, зовнішніх грантів, використання нових концепцій міського розвитку. Метою роботи є аналіз чинників розвитку міста Южне, оцінка ролі містоформуючих підприємств та визначення напрямків диверсифікаційних процесів у монофункціональному малому місті. Аналіз передумов розвитку малого монофункціонального міста Южне здійснено за індикаторами демографічного та соціально-економічного розвитку. Для оцінки містоформуючої ролі підприємств проаналізовано їх вплив на соціально-економічний розвиток міста за пропозицією робочих місць, будівництвом житла та об’єктів соціальної інфраструктури, долученістю до створення центру міста та облаштування його публічних просторів. Визначено, що диверсифікацію економіки малого монофункціонального міста Южне доцільно здійснювати за такими напрямками як розвиток інноваційних галузей на основі підготовки кваліфікованих кадрів у освітніх закладах та створення інноваційного парку, розвиток туризму та рекреації. Диверсифікація підходів до розвитку міста передбачає залучення різних акторів за рахунок місцевого активізму, зовнішніх грантів, використання нових підходів і концепцій міського розвитку. Позитивні зміни у розвитку малого монофункціонального міста Южне пов’язані із розробкою стратегій його розвитку на основі концепцій сталого розвитку, інтегрованого розвитку міста, інноваційного розвитку, розумного міста, зеленого міста, креативного міста, інклюзивного міста.
ДИВЕРСИФІКАЦІЯ СОЦІАЛЬНО-ЕКОНОМІЧНОГО ТА ПРОСТОРОВОГО РОЗВИТКУ МАЛОГО МОНОФУНКЦІОНАЛЬНОГО МІСТА – КЕЙС МІСТА ЮЖНЕ, УКРАЇНА
Keywords: small city; monofunctional city; diversification; urban planning; Yuzhne; Ukraine; мале місто; монофункціональне місто; диверсифікація; міське планування; Южне; Україна